Molecularly imprinted adsorbent as well as preparation method and application thereof
By preparing molecular imprinted adsorbents with multi-stage pore structures, the limitations of existing adsorbents in CO2 adsorption selectivity and capacity are solved, and efficient and selective CO2 adsorption is achieved, which is suitable for different application scenarios and alleviates the greenhouse effect.
Patent Information
- Application Number
- CN202510594854.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-09
- Publication Date
- 2025-08-08
- Estimated Expiration
- 2045-05-09
AI Technical Summary
The existing adsorbents have limitations in CO2 adsorption selectivity and adsorption capacity, which is difficult to meet environmental protection needs.
Functional monomers, crosslinking agents, initiators and linear polymers with weight ratios of 1:0.2-0.6:0.02-0.15:0.8-2 were mixed with solvents, and molecular imprinting adsorbents with multi-stage pore structures were prepared by spray drying and supercritical carbon dioxide treatment. Supercritical carbon dioxide was used as template molecules and foaming agents to perform self-assembly and crosslinking copolymerization.
It improves the adsorption capacity and adsorption rate of CO2, has a high selectivity and multi-stage pore structure, adapts to the needs of different application scenarios, alleviates the greenhouse effect and achieves carbon emission reduction.
Smart Images

Figure CN120437983A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of gas adsorbent materials, and in particular to a molecularly imprinted adsorbent and a preparation method and application thereof. Background Art
[0002] In recent years, the massive emission of carbon dioxide (CO2) has led to air pollution and the greenhouse effect, posing a serious threat to the Earth's environment, upon which humanity depends. Consequently, the efficient and selective adsorption of CO2 from mixed gases, such as industrial waste gas and atmospheric air, has become a research hotspot.
[0003] Traditional adsorbents have limitations in terms of adsorption selectivity and capacity, making them difficult to meet the growing demand for environmental protection. Molecular imprinting technology (MIT), also known as template molecule technology, is a new technology developed at the intersection of multiple disciplines, including polymer chemistry, biochemistry, chemical engineering, and materials science. MIT can produce materials with specific recognition and efficient adsorption capabilities for specific target molecules. This unique advantage has led to its widespread application in environmental treatment and analysis.
[0004] Molecularly imprinted CO2 adsorbent is a high-efficiency adsorbent with selective adsorption of CO2, designed and prepared based on the principle of molecular imprinting technology and the method of molecular self-assembly. It has the advantages of simple adsorbent preparation process, low energy consumption in the analysis process, and selective adsorption.
[0005] CN110743512A discloses a method for preparing a molecularly imprinted carbon dioxide adsorbent, characterized by the following steps: (1) carbonizing sieved sunflower biomass and then activating it to obtain activated carbon for later use; (2) using the biomass activated carbon from step (1) as a carrier, adding a template molecule and a functional monomer, and dissolving them in a mixed solvent, then adding a crosslinking agent and an initiator, sealing the reaction in an inert atmosphere, separating the solid product in the reaction system, washing, and drying to obtain a molecularly imprinted carbon dioxide adsorbent. This method uses activated carbon as a molecularly imprinted material carrier, providing a large specific surface area, which is conducive to the loading of the imprinted polymer and increasing the number of adsorption sites. At the same time, the molecularly imprinted adsorbent prepared by this method has high carbon dioxide selectivity and adsorption efficiency. However, this method uses oxalic acid or oxalic acid as the template molecule, and the adsorption rate and adsorption amount of the molecularly imprinted adsorbent for CO2 are relatively limited.
[0006] Therefore, developing a new molecularly imprinted adsorbent with high selectivity and adsorption efficiency is of great significance for achieving efficient adsorption of CO2. Summary of the Invention
[0007] The object of the present invention is to provide a molecularly imprinted adsorbent having high selectivity and high adsorption efficiency for CO2 adsorption.
[0008] In order to achieve the above object, the present invention provides a method for preparing a molecularly imprinted adsorbent, which comprises:
[0009] (1) mixing an adsorbent raw material with a solvent to obtain an intermediate I; the adsorbent raw material contains a functional monomer, a cross-linking agent, an initiator, and a linear polymer in a weight ratio of 1:0.2-0.6:0.02-0.15:0.8-2; and the solvent is selected from at least one of N,N-dimethylformamide, N,N-dimethylacetamide, and tetrahydrofuran;
[0010] (2) spray drying the intermediate I to obtain polymer microspheres;
[0011] (3) treating the polymer microspheres with supercritical carbon dioxide to obtain intermediate II;
[0012] (4) The intermediate II is subjected to an initiation treatment and a gradient pressure relief treatment in sequence to obtain the molecularly imprinted adsorbent; the conditions of the gradient pressure relief treatment include: first reducing the pressure to 4-7 MPa and holding for 10-20 seconds, and then reducing the pressure to 0.1-0.12 MPa.
[0013] The second aspect of the present invention provides a molecularly imprinted adsorbent prepared by the method described in the first aspect.
[0014] The third aspect of the present invention provides the use of the molecularly imprinted adsorbent described in the second aspect in the field of CO2 adsorption.
[0015] The present invention utilizes functional monomers, crosslinking agents, initiators, and linear polymers in a weight ratio of 1:0.2-0.6:0.02-0.15:0.8-2 as adsorbent raw materials. These are first mixed with a solvent and the resulting mixture is spray-dried to form polymer microspheres. The polymer microspheres are then treated with supercritical carbon dioxide, leveraging the triple effects of supercritical carbon dioxide as a swelling agent, template molecule, and foaming agent to prepare the molecularly imprinted adsorbent of the present invention. First, the polymer microspheres are placed in supercritical carbon dioxide to swell, allowing carbon dioxide molecules to penetrate the interior of the polymer microspheres and come into contact with the functional monomers. The carbon dioxide molecules act as template molecules and self-assemble with the functional monomers, thereby forming stable molecularly imprinted sites. Second, the resulting mixture is subjected to energy initiation, allowing the functional monomers to undergo crosslinking and copolymerization with the crosslinking agent. Subsequently, the supercritical carbon dioxide undergoes a phase transition under the specific conditions of the present invention, causing foaming within the polymer microspheres while simultaneously removing carbon dioxide molecules from the polymer microspheres. This results in the molecularly imprinted adsorbent of the present invention having a hierarchical pore structure.
[0016] Through the above technical solution, the present invention also has at least the following beneficial effects:
[0017] (1) The molecularly imprinted adsorbent provided by the present invention has a multi-level pore structure, and its large specific surface area significantly improves the adsorption capacity and adsorption rate of carbon dioxide.
[0018] (2) The molecular imprinting adsorbent provided by the present invention can adjust its pore structure according to actual application to meet the needs of different application scenarios.
[0019] (3) The molecularly imprinted adsorbent provided by the present invention uses supercritical CO2 as a template molecule and has a high adsorption selectivity for carbon dioxide, which is of great significance for alleviating the greenhouse effect and achieving carbon emission reduction goals. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 It is a schematic diagram of the preparation process of the molecularly imprinted adsorbent provided by the present invention. DETAILED DESCRIPTION
[0021] The endpoints of the ranges and any values disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoints of each range, the endpoints of each range and individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered to be specifically disclosed herein.
[0022] As mentioned above, the first aspect of the present invention provides a method for preparing a molecularly imprinted adsorbent, the method comprising:
[0023] (1) mixing an adsorbent raw material with a solvent to obtain an intermediate I; the adsorbent raw material contains a functional monomer, a cross-linking agent, an initiator, and a linear polymer in a weight ratio of 1:0.2-0.6:0.02-0.15:0.8-2; and the solvent is selected from at least one of N,N-dimethylformamide, N,N-dimethylacetamide, and tetrahydrofuran;
[0024] (2) spray drying the intermediate I to obtain polymer microspheres;
[0025] (3) treating the polymer microspheres with supercritical carbon dioxide to obtain intermediate II;
[0026] (4) The intermediate II is subjected to an initiation treatment and a gradient pressure relief treatment in sequence to obtain the molecularly imprinted adsorbent; the conditions of the gradient pressure relief treatment include: first reducing the pressure to 4-7 MPa and holding for 10-20 seconds, and then reducing the pressure to 0.1-0.12 MPa.
[0027] Preferably, in step (1), the functional monomer is selected from at least one of acrylamide, methacrylamide and N,N-dimethylacrylamide.
[0028] Preferably, in step (1), the cross-linking agent is selected from dimethylpropylene glycol and / or N,N'-methylenebisacrylamide.
[0029] Preferably, in step (1), the initiator is selected from azobisisobutyronitrile and / or benzophenone.
[0030] Preferably, in step (1), the linear polymer is selected from polyvinylidene fluoride and / or polyacrylonitrile.
[0031] Further preferably, in step (1), the weight ratio of the adsorbent raw material to the solvent is 1:2.5-4.
[0032] Particularly preferably, in step (1), the mixing conditions include: temperature of 25-35° C. and time of 4-8 h.
[0033] In step (1) of the present invention, there is no particular requirement for the mixing speed, as long as the adsorbent raw materials can be mixed evenly. For example, the mixing speed can be 500-2000 rpm.
[0034] According to a preferred embodiment, in step (2), the conditions of the spray drying treatment include: an air inlet temperature of 110-130°C, an air outlet temperature of 80-90°C, and a feed rate of 4-6 mL / min.
[0035] According to a more preferred embodiment, in step (3), the supercritical carbon dioxide treatment conditions include: a pressure of 8-12 MPa, a temperature of 35-45°C, and a time of 2-6 hours. The inventors of the present invention have found that, under this preferred embodiment, the molecularly imprinted adsorbent prepared by the present invention has a higher carbon dioxide adsorption efficiency.
[0036] According to a preferred embodiment, in step (4), the initiation treatment is a photo-initiation treatment and / or a thermal initiation treatment; the conditions of the photo-initiation treatment include: a wavelength of 360-380 nm and a time of 0.5-2 h; the conditions of the thermal initiation treatment include: a temperature of 60-70° C. and a time of 6-30 h.
[0037] Preferably, in step (4), the pressure relief rate of the gradient pressure relief treatment is 1-2 MPa / min.
[0038] According to a particularly preferred embodiment, the preparation process of the molecularly imprinted adsorbent is as follows Figure 1 As shown, specifically:
[0039] (1) The functional monomer, crosslinking agent, initiator and linear polymer in a weight ratio of 1:0.2-0.6:0.02-0.15:0.8-2 are mixed with a solvent, and stirred at 25-35°C for 4-8 hours to obtain intermediate I (i.e. Figure 1 mixed solution in );
[0040] (2) spray drying the intermediate I (i.e., granulation) to obtain polymer microspheres; the spray drying conditions include: an air inlet temperature of 110-130° C., an air outlet temperature of 80-90° C., and a feed rate of 4-6 mL / min;
[0041] (3) placing the polymer microspheres in a high-pressure reactor and performing a swelling treatment under supercritical carbon dioxide conditions to obtain an intermediate II; the specific conditions of the swelling treatment include: a pressure of 8-12 MPa, a temperature of 35-45° C., and a time of 2-6 hours;
[0042] (4) The intermediate II is subjected to an initiation treatment and a gradient pressure reduction treatment in sequence to obtain the molecularly imprinted adsorbent; the initiation treatment can be selected from a photo-initiation treatment and / or a thermal initiation treatment, and after the initiation treatment, the functional monomer in the intermediate II undergoes cross-linking copolymerization with the cross-linking agent; the conditions for the photo-initiation treatment include: a wavelength of 360-380 nm and a time of 0.5-2 h; the conditions for the thermal initiation treatment include: a temperature of 60-70 ° C and a time of 6-30 h; the conditions for the gradient pressure reduction treatment include: first reducing the pressure to 4-7 MPa and maintaining it for 10-20 s, and then reducing the pressure to 0.1-0.12 MPa.
[0043] As mentioned above, the second aspect of the present invention provides a molecularly imprinted adsorbent prepared by the method described in the first aspect.
[0044] Preferably, the molecularly imprinted adsorbent has a multi-level pore structure.
[0045] According to a preferred embodiment, the distribution of pores of different sizes in the multi-level pore structure is as follows: the number of micropores with a pore diameter in the range of 0.1-5 μm accounts for 10-20% of the total number of pores, the number of mesopores with a pore diameter in the range of 5-10 μm accounts for 30-45% of the total number of pores, and the number of pores with a pore diameter above 10 μm accounts for 35-60% of the total number of pores.
[0046] As mentioned above, the third aspect of the present invention provides the use of the molecularly imprinted adsorbent described in the second aspect in the field of CO2 adsorption.
[0047] The present invention will be described in detail below by way of examples. In the following examples, unless otherwise specified, all instruments and raw materials used are commercially available.
[0048] Example 1
[0049] (1) 4 g of acrylamide, 1.5 g of dimethylpropylene glycol, 0.1 g of azobisisobutyronitrile, and 5.5 g of polyvinylidene fluoride were weighed and added to 30 mL of N,N-dimethylformamide solution. The mixture was stirred at 1000 rpm at 30°C for 5 h to obtain intermediate I.
[0050] (2) The intermediate I was transferred to a spray dryer, and the air inlet temperature was set to 120°C, the air outlet temperature was set to 80°C, and the feed rate was set to 5 mL / min to obtain polymer microspheres.
[0051] (3) The polymer microspheres were placed in a high-pressure reactor, supercritical carbon dioxide was introduced, and the reaction was maintained at a pressure of 10 MPa and a temperature of 40°C for 5 h to obtain intermediate II.
[0052] (4) The autoclave was placed at 60°C, and the intermediate II was subjected to an initiation treatment for 24 hours, followed by a gradient pressure release treatment, specifically: the pressure was first adjusted to 6 MPa at a pressure release rate of 1.5 MPa / min, maintained for 10 seconds, and then the pressure was reduced to 0.1 MPa at the same pressure release rate to obtain a molecularly imprinted adsorbent-I.
[0053] Example 2
[0054] (1) 4.5 g of acrylamide, 2.0 g of dimethylpropylene glycol, 0.2 g of benzophenone, and 6 g of polyacrylonitrile were weighed and added to 35 mL of N,N-dimethylacetamide. The mixture was stirred at 1500 rpm at 35°C for 4 h to obtain intermediate I.
[0055] (2) The intermediate I was transferred to a spray dryer, and the air inlet temperature was set to 130°C, the air outlet temperature was set to 85°C, and the feed rate was set to 6 mL / min to obtain polymer microspheres.
[0056] (3) The polymer microspheres were placed in a high-pressure reactor, supercritical carbon dioxide was introduced, and the reaction was maintained at a pressure of 12 MPa and a temperature of 45°C for 6 h to obtain intermediate II.
[0057] (4) The intermediate II was induced to undergo treatment under light of 365 nm for 1 h, and then a gradient pressure relief treatment was started, specifically: the pressure was adjusted to 7 MPa for the first time, maintained for 10 s, and then reduced to 0.1 MPa for the second time to obtain a molecularly imprinted adsorbent-II.
[0058] Example 3
[0059] This example was carried out using a method similar to that of Example 1, except that in step (3), after the supercritical carbon dioxide was introduced, the supercritical carbon dioxide treatment conditions were adjusted to: a pressure of 7.5 MPa and a temperature of 32° C. for 6 h to obtain Intermediate II. The remaining operations were the same as those of Example 1 to prepare Molecularly Imprinted Adsorbent-III.
[0060] Comparative Example 1
[0061] This comparative example was carried out using a method similar to that of Example 1, except that in step (3), supercritical carbon dioxide was not introduced. Instead, the polymer microspheres were directly placed in an autoclave, nitrogen was introduced, and the pressure was set at 10 MPa and the temperature was maintained at 40°C for 5 hours to obtain Intermediate II. The remaining operations were the same as those of Example 1 to prepare a molecularly imprinted adsorbent-DI.
[0062] Comparative Example 2
[0063] This comparative example was carried out using a method similar to that of Example 1, except that in step (4), the product after the initiation treatment was subjected to a one-step pressure release treatment, specifically: the high-pressure reactor was placed at 60° C., the intermediate II was subjected to an initiation treatment for 24 h, and then the pressure release treatment was started, and the pressure was directly released to 0.1 MPa at a pressure release rate of 1.5 MPa / min to obtain a molecularly imprinted adsorbent -DII.
[0064] Comparative Example 3
[0065] This comparative example was carried out using a method similar to that of Example 1, except that in step (1), the amount of the linear polymer polyvinylidene fluoride was adjusted to 8.5 g. The remaining steps and conditions were the same as those of Example 1 to obtain a molecularly imprinted adsorbent-DIII.
[0066] Comparative Example 4
[0067] This comparative example was carried out using a method similar to that of Example 1, except that in step (4), the conditions of the gradient pressure relief treatment were adjusted as follows: the pressure was adjusted to 3 MPa at a pressure relief rate of 1.5 MPa / min, maintained for 10 s, and then the pressure was reduced to 0.1 MPa while maintaining the same pressure relief rate to obtain a molecularly imprinted adsorbent-DIV.
[0068] Test Case
[0069] The CO2 adsorption performance of the molecularly imprinted adsorbents prepared in the above examples was tested, specifically:
[0070] In this test, a fully automated physical adsorption instrument was used to measure CO2 adsorption. Each molecularly imprinted adsorbent was heated in a degassing station to remove residual moisture and gas, activating the sample. The sample was then exposed to CO2 gas and measured at a temperature of 25°C and a pressure of 0.1 MPa. The CO2 / N2 separation factor was determined using an adsorption equilibrium experiment at 25°C and a pressure of 0.1 MPa.
[0071] The test results are shown in Table 1.
[0072] Table 1
[0073] <![CDATA[CO2 adsorption capacity (mmol / g)]]> Separation factor Molecularly imprinted adsorbent-I 19.5 90 Molecularly imprinted adsorbent-II 18.8 85 Molecularly imprinted adsorbent-III 14.5 75 Molecularly Imprinted Adsorbent-DI 6.2 42 Molecularly imprinted adsorbent-DII 5.8 63 Molecularly imprinted adsorbent-DIII 6.5 65 Molecularly Imprinted Adsorbent-DIV 7.2 70
[0074] From the results in Table 1, it can be seen that the molecularly imprinted adsorbent prepared by the present invention has significantly better effects in terms of CO2 adsorption selectivity and adsorption capacity, reflecting its excellent carbon dioxide adsorption performance.
[0075] The preferred embodiments of the present invention have been described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, various simple variations of the technical solution of the present invention may be made, including combining the various technical features in any other appropriate manner. These simple variations and combinations should also be regarded as disclosed in the present invention and fall within the scope of protection of the present invention.
Claims
1. A method for preparing a molecularly imprinted adsorbent, characterized in that: The method includes: (1) mixing an adsorbent raw material with a solvent to obtain an intermediate I; the adsorbent raw material contains a functional monomer, a cross-linking agent, an initiator, and a linear polymer in a weight ratio of 1:0.2-0.6:0.02-0.15:0.8-2; and the solvent is selected from at least one of N,N-dimethylformamide, N,N-dimethylacetamide, and tetrahydrofuran; (2) spray drying the intermediate I to obtain polymer microspheres; (3) treating the polymer microspheres with supercritical carbon dioxide to obtain intermediate II; (4) The intermediate II is subjected to an initiation treatment and a gradient pressure relief treatment in sequence to obtain the molecularly imprinted adsorbent; the conditions of the gradient pressure relief treatment include: first reducing the pressure to 4-7 MPa and holding for 10-20 seconds, and then reducing the pressure to 0.1-0.12 MPa.
2. The method according to claim 1, wherein In step (1), the functional monomer is selected from at least one of acrylamide, methacrylamide and N,N-dimethylacrylamide; And / or, the cross-linking agent is selected from dimethylpropylene glycol and / or N,N'-methylenebisacrylamide.
3. The method according to claim 1, wherein In step (1), the initiator is selected from azobisisobutyronitrile and / or benzophenone; And / or, the linear polymer is selected from polyvinylidene fluoride and / or polyacrylonitrile.
4. The method according to claim 1, wherein In step (1), the weight ratio of the adsorbent raw material to the solvent is 1:2.5-4.
5. The method according to claim 1, wherein In step (2), the conditions for the spray drying treatment include: an air inlet temperature of 110-130° C., an air outlet temperature of 80-90° C., and a feed rate of 4-6 mL / min.
6. The method according to claim 1, wherein In step (3), the conditions for the supercritical carbon dioxide treatment include: pressure of 8-12 MPa, temperature of 35-45° C., and time of 2-6 h.
7. The method according to claim 1, wherein In step (4), the initiation treatment is a photo-initiation treatment and / or a thermal initiation treatment; The conditions of the light initiation treatment include: wavelength of 360-380nm, time of 0.5-2h; The conditions of the heat initiation treatment include: a temperature of 60-70° C. and a time of 6-30 hours.
8. A molecularly imprinted adsorbent prepared by the method according to any one of claims 1 to 7.
9. The molecularly imprinted adsorbent according to claim 8, wherein The molecularly imprinted adsorbent has a multi-level pore structure.
10. Use of the molecularly imprinted adsorbent according to claim 8 or 9 in the field of CO2 adsorption.
Citation Information
Patent Citations
Method for preparing tissue engineering scaffold with double-pore structure by combining with supercritical carbon dioxide foaming technology
CN103254459A
Preparation and regeneration method and application of carbon dioxide molecularly imprinted adsorbent
CN110743512A
Methods for production of selective synthetic polymeric adsorbents
GB2586340A
Method for preparing molecularly imprinted polymers (MIP) through radical polymerisation
US20120100358A1